2023
DOI: 10.1002/mabi.202200521
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Abdominal Wall Defect with Composite Scaffold of 3D Printed ADM/PLA in a Rat Model

Abstract: Abdominal wall defects are a frequently occurring condition in surgical practice. The most important are material structure and biocompatibility. In this study, polylactic acid (PLA) mesh composited with a 3D printing of acellular dermal matrix (ADM) material is used to repair abdominal wall defects. The results show that the adhesion score of ADM/PLA composite scaffolds is smaller than PLA meshes. Immunohistochemical assessment reveals that the ADM/PLA composite scaffold can effectively reduce the inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…With these advantages in mind, numerous researchers approached 3D printing to generate novel mesh designs with improved performance. Several studies reported on the production of promising 3D-printed meshes, including composite polylactic acid-acellular dermal matrix scaffolds [83], personalized polypropylene-polyvinyl alcohol meshes loaded with ciprofloxacin [84], drug-doped polycaprolactone meshes containing alginate and gentamicin [85], tailored meshes made of alginate and waterbornepolyurethane [86], and custom polycaprolactone constructs impregnated with iodinated, gadolinium, and barium contrast agents [87].…”
Section: Novel Mesh Designsmentioning
confidence: 99%
“…With these advantages in mind, numerous researchers approached 3D printing to generate novel mesh designs with improved performance. Several studies reported on the production of promising 3D-printed meshes, including composite polylactic acid-acellular dermal matrix scaffolds [83], personalized polypropylene-polyvinyl alcohol meshes loaded with ciprofloxacin [84], drug-doped polycaprolactone meshes containing alginate and gentamicin [85], tailored meshes made of alginate and waterbornepolyurethane [86], and custom polycaprolactone constructs impregnated with iodinated, gadolinium, and barium contrast agents [87].…”
Section: Novel Mesh Designsmentioning
confidence: 99%
“…In recent years, decellularized dermal matrix tamponades have been widely used in the treatment of anal fistula. In addition, with the continuous development of 3D bioprinting technology and the application of biological scaffold materials, new ideas have been opened for the treatment of anal fistula by tissue engineering. − …”
Section: The Application Of Decellularized Scaffolds In Tissue Engine...mentioning
confidence: 99%
“…[4,241] Statistics indicate that post-operative infectious complications related to AWH have a frequency of around 1%∟4%. [175,184,242] Though AWHPMs are sterilized before using, bacterial growth around the patches-AW is unavoidable due to an external bacterial infection or inadequate disinfection caused by human error during the procedure. [242] Inappropriate antimicrobial approaches can extend the period of inflammation and increase the levels of inflammatory factors, thereby prolonging the healing time.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%